Case-Based Specialty Training for Medical Students to Elicit Social Determinants of Health - Danielle Howell; Ellen Pearlman; Rebecca Dougherty; John Paul Sánchez; Melissa Pawelczak; Alice Fornari; Joseph S. Weiner; Robert O. Roswell (Association of American Medical Colleges, 2024)
Introduction Without explicit education and training on how social determinants of health (SDoH) impact patient care and health outcomes, medical schools are failing to effectively equip future physicians to serve their patients. We created this workshop on health equity with a focus on SDoH to help students more effectively communicate with diverse populations. Methods Third-year medical students and faculty were provided with class guides, learning objectives, role-play vignettes containing clerkship-specific history and physical exams, schedules, and discussion questions during a 2-hour session centered on SDoH. The workshop's impact was measured through mixed-methods analysis of surveys. Results Based on pre- and postsurvey results from 87 participants, medical students strongly agreed that (1) SDoH factor more into a patient's health outcomes than the clinical encounter (pre: 67%, post: 87%), (2) it is their duty to gather information about SDoH (pre: 86%, post: 97%), (3) neighborhood safety is one of the key SDoH (pre: 88%, post: 97%), (4) they understood the impact of upstream interventions (pre: 35%, post: 93%), (5) they could efficiently screen all patients for SDoH at every medical encounter (pre: 27%, post: 86%), and (6) they could find preliminary resources to quickly assist patients in need of help regarding particular SDoH (pre: 26%, post: 85%). Discussion This was the first iteration of this workshop; challenges involved piloting the content, time restraints, and organizational structure of the workshop design. Future directions include making SDoH curricula an integral part of undergraduate medical education and diverse clinical environments.